1999
DOI: 10.1182/blood.v93.3.780.403k37_780_786
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Derived In Vitro From Acute Myelogenous Leukemia Cells Stimulate Autologous, Antileukemic T-Cell Responses

Abstract: We have previously reported that leukemic dendritic cells (DC) can be generated ex vivo from myelomonocytic precursors in chronic myelogenous leukemia. In this study we report the generation of DC from acute myelogenous leukemia (AML) cells and their potent ability to stimulate leukemia-specific cytolytic activity in autologous lymphocytes. DC were generated in vitro using granulocyte-macrophage colony-stimulating factor +interleukin-4 in combination with either tumor necrosis factor- or CD40 ligand (CD40L). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 12 publications
4
79
0
1
Order By: Relevance
“…Recent reports have shown that the same might become possible for patients with AML [8, 9, 15, 16]. Although the success of DC cultures varied from patient to patient, leukemic DC could be generated in two‐thirds of the patients in our study.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…Recent reports have shown that the same might become possible for patients with AML [8, 9, 15, 16]. Although the success of DC cultures varied from patient to patient, leukemic DC could be generated in two‐thirds of the patients in our study.…”
Section: Resultsmentioning
confidence: 51%
“…The stimulation of a primary naive T‐cell response stresses the functional capacity of those cells. Induction of specific antileukemic T‐cell activity by priming with leukemic DC was reported by other investigators [9]. We tried to reduce the influence of contaminating B cells and monocytes by performing fluorescence‐activated or immunomagnetic enrichment of CD1a + /CD14 – DC to a purity of more than 80%.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…70 Myeloid progenitors obtained from patients with AML differentiated to enhanced antigenpresenting cells when treated in vitro with GM-CSF, TNF, IL-4, CD40 ligand, Flt3, or SCF. 71 Likewise, others have reported similar results after GM-CSF, TNF, and IL-4 culture of cells obtained from patients with AML and CML; 72,73 and Coleman et al reported the restoration of costimulatory molecules on GM-CSF and IL-4-incubated T-cells obtained from patients with CML. 74 In a series of interrelated trials reported by Bedi et al and Jones et al, CML progenitor cells were eliminated preferentially from culture through terminal differentiation in the presence of hematopoietic growth factors.…”
Section: Hematologic Malignanciesmentioning
confidence: 67%